Enhancement of para-selectivity in the phenol oxidation with H2O2 over Ti-MCM-68 zeolite catalyst. Issue 3 (9th September 2015) - Inagaki, S.; Tsuboi, Y.; Sasaki, M.; Mamiya, K.; Park, S.; Kubota, Y.
Abstract : Si-modified Ti-MCM-68 catalyst showed very high para -selectivity as well as high activity for phenol oxidation in the presence of EtOH as a cosolvent. Abstract : Although titanium silicalite-1 (TS-1) with anMFI framework (interconnected 10-ring micropores) is a useful catalyst for phenol oxidation, Ti-MCM-68, a novelMSE -type titanosilicate with 12-ring and 10-ring micropores, has been developed as a phenol oxidation catalyst with high activity and selectivity toward the p -isomer, hydroquinone. This report describes the improvement in catalytic activity and para -selectivity of Ti-MCM-68 for phenol oxidation. Thermal treatment after Ti insertion significantly enhanced the catalytic activity of Ti-MCM-68, mainly due to an improvement in the hydrophobicity in the micropores. Silylation of the external surface of Ti-MCM-68 with Ph2 SiCl2, followed by Ti insertion and calcination, showed greater para -selectivity, indicating that the selective formation of p -isomers occurred within one-dimensional 12-ring micropores in the Ti-MCM-68. The addition of ethanol as a cosolvent to the reaction mixture resulted in the best para -selectivity (>94%) and activity among the modified Ti-MCM-68 catalysts.